Pattern of Occlusal Contacts in Lateral Excursions (Canine Protection or Group Function) - Sapkota, B; Gupta, A (Kathmandu University Medical Journal, 2015)
Background Establishing or providing occlusion that successfully permits efficient masticatory function is basic to dentistry. To maintain harmony of the occlusal condition, the posterior teeth must pass close to but not contact their opposing teeth during mandibular movement. Anterior guidance is essential to a harmonious functional relationship in the masticatory system. Objective The objective of this study was to find out the frequency of pattern of occlusal contacts in lateral position and to compare the accuracy of shim-stock and articulating paper. Method This study was conducted in the Department of Prosthodontics, Kathmandu University School of Medical Sciences. The study consisted of 80 healthy subjects between the age group of 18-30 years. They were selected randomly from undergraduate students and dental hygienist of college of dental science and written consent was taken. This age was selected because of minimal occlusal wear. Results In the present study with 80 participants the majority of the contact patterns with shimstock on the working side were group function( 84%), the canine protected occlusal patterns were found to be 12% and the unclassifiable pattern were found to be 4%. On the other hand, the data with articulating paper were group function type (94%), the canine protected occlusal patterns as 2.5% and the unclassifiable pattern were found to be 3.5%. In this study, with shim stock, the majority of the contact patterns were group function being 84% whereas with the articulating paper it was 94%. When shim stock occlusal strip (12 ?m thick) was compared to commonly used articulating paper (40 ?m), the excessive thickness of articulating paper that exceed the maximum recommended thickness of occlusal recording strips markedly must have given much more false contacts. Conclusion It was concluded that the majority of the contact pattern were group function being 84% with shim stock and 94% with articulating paper. Also shim stock exhibits superior accuracy and reliability. Kathmandu University Medical Journal Vol.12(1) 2014: 43-47